2022
DOI: 10.1039/d2gc02990a
|View full text |Cite
|
Sign up to set email alerts
|

Redox-neutral synthesis of π-allylcobalt complexes from alkenes for aldehyde allylation via photoredox catalysis

Abstract: This work reports the first visible-light mediated cobalt-catalyzed aldehyde allylation with simple alkenes to produce homo-allylic alcohols. This novel strategy directly uses easily available unactivated alkenes as allyl sources instead of pre-synthesized allylic halides.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 53 publications
(65 reference statements)
0
7
0
Order By: Relevance
“…As we have already remarked in the Introduction, the better reducing properties of 2 were the key for the reaction, while 3DPAFIPN or 4CzIPN were not suitable. The cobalt salt, the photocatalyst, Hantzsch’s ester, and irradiation with visible light are all required for a successful reaction.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As we have already remarked in the Introduction, the better reducing properties of 2 were the key for the reaction, while 3DPAFIPN or 4CzIPN were not suitable. The cobalt salt, the photocatalyst, Hantzsch’s ester, and irradiation with visible light are all required for a successful reaction.…”
Section: Resultsmentioning
confidence: 99%
“…On the basis of the experiments performed, we can suggest the mechanistic picture depicted in Figure . In recent years, several authors have suggested that the reaction follows a Co­(II)–Co­(I)–Co­(III)–Co­(II) cycle. ,,, Co­(II) is reduced by 2 in its excited state [E­( 2 •+ /* 2 ) = −1.31 vs SCE] to Co­(I) { E [Co­(II)/Co­(I)] = −1.05 V vs SCE} that is reacting with allyl acetate to form a Co­(III) allyl intermediate. The Co­(III) allyl is then further reduced by a SET event ( 2 or HE •+ ) to Co­(II) allyl, the reactive organometallic species that can react with aldehydes by a Zimmerman–Traxler transition state…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2022/2023, the Shi group reported the formation of a reactive allylcobalt by photoredox catalysis under the framework of a radical-to-polar crossover (Scheme 24 ). 116 117…”
Section: Cobalt Nucleophilic Organometallic Reagentsmentioning
confidence: 99%
“…In 2022/2023, the Shi group reported the formation of a reactive allylcobalt by photoredox catalysis under the framework of a radical-to-polar crossover (Scheme 24). 116,117 They investigated the possibility of using the redox neutral system employed by the Glorius group 23 and Kanai, Mitsunuma, and co-workers 53 based on the formation of the allyl radical by oxidation of a C=C and deprotonation. Since the reduction potential of the cobalt complexes are lower compared to chromium, this limits the selection of suitable photoredox complexes for the reaction.…”
Section: Allylation Reactionsmentioning
confidence: 99%